Caracterização da descendência híbrida e segregação de marcadores microssatélites em uma população F2 de Prunus sp - Machado, Luciana Rodrigues Nogueira (2011)
The peach (Prunus persica (L) Batsch) is the predominant stone fruit around the world, but in Brazil, due to factors such as incidence of pests in orchards, low quality plant propagation material and the lack of suitable rootstocks culture, the productivity is still considered low. In this context, is necessary to develop new rootstocks of Prunus, more adapted to the ecological conditions of the Southern region of Brazil and carrying genes for pests resistance such as nematodes. In this study, microsatellite loci (SSR) were used to verify the hybrid offspring of genotypes and makers segregation in an F2 population of peach rootstocks, obtained from controlled crosses, generating data to marker-assisted selection (MAS) of new genotypes carrying genes for nematode resistance. This work was divided in two articles; the first was a paternity test to verify the paternal and maternal offspring of 13 hybrids from controlled crosses between several rootstocks and scion with desirable agronomic traits. We obtained confirmation of paternity for 11 of the 13 hybrids analyzed. Two genotypes, presumably descendants of Prunus mume as male parent, were confirmed as being generated by selfing of genotipe Aldrighi P1. In the second article, a linkage map was constructed for a population of 50 F2 plants obtained by selfing of F1 hybrid, derived from a cross between the peaches Capdeboscq‟ x Flordaguard'. The segregation of 37 SSR loci was evaluated and 11 markers showed a link, allowing us to build a map with two groups. It was found that the markers BPPCT004, CPDCT044, BPPCT034 and BPPCT002 were grouped in a manner similar to that found in the GL2 Prunus reference map. With the data obtained suggests that these SSR loci are associated with genes for resistance to Meloidogyne spp. in different mapping populations, in which case inherited from the rootstock 'Flordaguard', and may be used directly in SAM and improvement genetic peach rootstocks derived from a cross between Capdeboscq‟ x Flordaguard‟.